Advances in Photodynamic Therapy Based on Nanotechnology and Its Application in Skin Cancer - Zhang, Ping; Han, Ting; Xia, Hui; Dong, Lijie; Chen, Liuqing; Lei, Li (Frontiers in Oncology, 2022)
Comprehensive cancer treatments have been widely studied. Traditional treatment methods (e.g., radiotherapy, chemotherapy), despite ablating tumors, inevitably damage normal cells and cause serious complications. Photodynamic therapy (PDT), with its low rate of trauma, accurate targeting, synergism, repeatability, and relative low cost, has displayed great advantages in the treatment of tumors. In recent years, nanotech-based PDT has provided a new modality for cancer treatment. Direct modification of PSs by nanotechnology or the delivery of PSs by nanocarriers can improve their targeting and specificity for tumors. In this review, we strive to provide the reader with a comprehensive overview, on various aspects of the types, characteristics, and research progress of photosensitizers and nanomaterials used in PDT. And the application progress and relative limitations of nanotech-PDT in non-melanoma skin cancer and metastatic melanoma are also summarized.